LABOUR MARKET AND ECONOMIC CRIMES: AN INVESTIGATION FROM FIFTY U.S STATES AND THE DISTRICT OF COLUMBIA - Xinyuan Yang (The Institute of Academic Research and Publication (IARP), 2022)
Crime is a serious and complex problem that affects both the social and economic development of a country. An investigation studying not only the determinants of crime but also the relationship between crime and economic phenomena such as employment, income, and immigration, is necessary. The purpose of this empirical report is to investigate the relationship between labor market conditions and economic crimes in the fifty U.S. states and the District of Columbia by building upon the economic model of rational behavior. A very intuitive hypothesis is that an agent is more likely to engage in criminal activity if there is a low level of deterrence (e.g. minimal police enforcement, absence of death penalty, etc.) and unfavorable economic conditions (e.g. high unemployment rate, low educational attainment, low GDP per capita). There are also various socioeconomic variables such as age distribution, church attendance, immigration, urbanization, and racial mix that reflect an individual’s tastes and thus influence behavior.